O sentido da linguagem cinematográfica em Serra Pelada, a lenda da montanha de ouro, de Víctor Lopes (2013) (TEL Tempo, Espaço e Linguagem, 2022)
This work is an attempt to examine the cinematographic language and the meaning that can be represented in the construction of the film The legend mountain of gold (2013), by Victor Lopes as a tool to understand composite concepts as an interdisciplinary communication approach in which the aesthetics represented in images described in text are and can reveal as visual experiences provided from the subjects' historical and cultural context. Using the methodologies observed from Marcel Martin and Relivaldo Pinho to support the dynamics of the composition of the aesthetic characteristics of real, material and figurative value that expose cinema as the art of expressiveness of the creative and revealing affection attitude.